Governance of Aquatic Systems: What Attributes and Practices Promote Resilience? - Plummer, Ryan; Baird, Julia; Moore, Michele-Lee; Brandes, Oliver; Imhof, Jack; Krievins, Katrina (International Journal of Water Governance, 2014)
Aquatic environments embody the characteristics of complex social-ecological systems and as pressures on them intensify so does concern about their resilience. Resilience research has advanced the conceptual understanding of how aquatic systems function and underscored the need for an adaptive approach to management. More recently, a growing emphasis has been placed on resilience concepts in relation to water governance and thereby the broader social, political, and economic contexts in which aquatic systems are embedded. Using a two round online Delphi survey of global experts and water governance, this study identifies governance attributes that support specified and general resilience in aquatic systems, and describes practices or activities that enhance governance ability to respond to shocks and disturbances. The results of the Delphi study offer a prioritized list of attributes of governance for aquatic system governance resilience, including being adaptive, polycentric, inclusive and maintaining strong leadership. Similar to the attributes described in the existing literature on resilience and water governance, those identified through the Delphi remain somewhat abstract. This research highlights the need for future studies exploring how these concepts can be applied in practice and the extent to which they can be traded off.